Intelligent robotic navigation - Nurhaqim Mohammad (2019)
One interesting Speaker, Mr. Gonzalo Ferrer – SKOLTECH [5] mentioned that robot barely perceive the world, which is formidably complex and process this limited data to plan their motions. And one can also argue that on simple scenarios, the task of navigating is completely solved. Nonetheless, full autonomy in robotics has not arrived yet.